1997
DOI: 10.1074/jbc.272.12.7867
|View full text |Cite
|
Sign up to set email alerts
|

The Active Sites of Fructose 6-Phosphate,2-kinase: Fructose-2,6-bisphosphatase from Rat Testis

Abstract: To investigate the role in catalysis and/or substrate binding of the Walker motif residues of rat testis fructose 6-phosphate,2-kinase:fructose-2,6-bisphosphatase (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 38 publications
4
23
1
Order By: Relevance
“…For competition assays, 0.4 M motors were incubated with 2 M Mt and 2 M mADP and titrated against varying concentrations of unlabeled ADP. The IC 50 , defined as the [ADP] where the fluorescence signal drops to 50%, was fit using Morrison's quadratic equation (31),…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For competition assays, 0.4 M motors were incubated with 2 M Mt and 2 M mADP and titrated against varying concentrations of unlabeled ADP. The IC 50 , defined as the [ADP] where the fluorescence signal drops to 50%, was fit using Morrison's quadratic equation (31),…”
Section: Methodsmentioning
confidence: 99%
“…From the IC 50 , the relationship between the equilibrium binding constants for mADP and ADP was obtained using the Cheng-Prusoff equation (32),…”
Section: Methodsmentioning
confidence: 99%
“…A function in liganding to M values increase by Ϸ20-fold for ATP and Ϸ40-fold for mevalonate. Effects of this magnitude have been observed upon replacement of carboxyl groups that function as cation ligands in phosphofructokinase (25), 6-phosphofructo-2-kinase (22), and phosphoribulokinase (26). If the assignment of Glu-193 as cation ligand is correct, then, in the absence of any other invariant acidic residues that can be clearly be implicated in catalysis, a serine/threonine residue would be a plausible candidate for the role of second cation ligand.…”
Section: An Active Site Serine In Mevalonate Kinasementioning
confidence: 99%
“…Another potential active site role for alcohol functionalities in phosphotransferase reactions involves H-bonding to oxygens of the phosphoryl chain of ATP substrate (18 -20). Elimination of the side chain in such enzymes can produce a k cat effect (21,22) even larger than typically generated upon elimination of a cation ligand. Alignment of available deduced sequences for eukaryotic and prokaryotic mevalonate kinases indicates only four invariant residues (Ser-145, Ser-146, Ser-201, Thr-243) with alcohol groups in their side chains (Fig.…”
Section: Mutagenic Substitution Of Alcohol Sidementioning
confidence: 99%
“…Previously, we cloned a gene specifically expressed in human testis [8] that corresponds to the pfkfb4 gene [7] and encodes the testes PFK-2 isozyme [9,10]. Recently, it has been demonstrated that pfkfb4 gene has a strong response to hypoxic stimulation [11].…”
Section: Introductionmentioning
confidence: 99%